Elements of the Crime of Arbitrariness in Using Power - Sami Noman, Researcher. Muhammad; Abdel Reda Aflouk, Prof.Dr. Muhammad Ali (Basra studies journal, 2025)
Nowadays one can clearly see that many employees take advantage of the autherity granted to them to cause harm and damage to people who seek to achieve and play their positive role in purging the administrative apparatus of people who seek to distort its reputation and exploit it in a manner that violates the spirit of law. Therefore, the abuse of power results in a criminal threat that undermines confidence in the administrative apparatus, in addition to the weakness or lack of efficiency and effectiveness that must characterize the administration by fighting and removing an honest employee and bringing in an employee characterized by corruption. For this reason, the Iraqi legislator dealt with this crime with punitive provisions, and imposed criminal liability on it by drafting the text of Article (329/Third) of the amended Iraqi Penal Code No. 111 of 1969. The importance of this study is highlighted in that it was drawn up after political developments occurred in Iraq. After the year 9/4/2003 and the shift from the socialist dictatorial system that favored senior employees and which worked to politicize the administrative apparatus and put employees on the basis of party affiliation rather than competence and merit, towards a liberal democratic system that sanctifies freedoms and guarantees rights.